Modern Realities of the Tourism Market of Ukraine During the Coronavirus Period: Challenges and Practical Solutions - Бєлоусова, Наталія Володимирівна; Скоростецька, Ольга Олександрівна (Київський національний університет імені Тараса Шевченка, 2020)
Purpose. To consider the problems of the tourism market in modern conditions, the crown of the viral period, with an emphasis on adapting the mechanism of tourist services, restructuring consciousness and looking for ways to optimize the implementation of new approaches in the practical work of travel agencies and higher educational institutions that train specialists in the tourism industry. Methodology. Analytical, statistical, comparative-geographical and synthetic methods were used. Results. The main conceptual issues on the problems of the existence of the tourist sphere of Ukraine during the corona of the virus were voiced at the remote scientific and practical conference "Ukrainian tourism in the conditions of the corona and post corona of the viral period: anti-crisis scenarios, international experience, best practices", which was organized with the assistance of the department Geography of Ukraine and the Department of Regional Studies and Tourism of the Taras Shevchenko National University of Kyiv, to which experts-practitioners of the tourism industry, representatives of state institutions related to tourism, teachers of universities in the city of Kiev and Ukraine were invited. Scientific novelty. As part of the modern life of mankind, corrected by the latest outbreak of the global pandemic COVID-19, a number of problems of economic, political, social, economic, educational and general human nature have arisen, the solution of which requires a significant rethinking of the existing situation in society and the provision of proposals for a new format for future life humanity and, in particular, in Ukraine. Taking into account the peculiarities of tourism development in each individual country, the priority planned actions should be the development and implementation of the "Roadmap for Tourism Development in Ukraine", which will spell out the main provisions for the practical implementation of the program during the corona virus and the stage of exit from the post-coronavirus period. The article analyzes the international experience in the implementation of such programs, evaluates the factual material concerning the introduction of the "Road Map" in the conditions of the Ukrainian tourist market. Practical significance. The article raises difficult issues related to the realities of modern life of people within the framework of the tourism sector of Ukraine, with its problems, challenges and practical solutions. The publication materials can be used in the educational process in higher educational institutions that train specialists for the Ukrainian tourism industry, the practical activities of travel operators and agencies, in the process of work of departments and professional institutions, relate to the tourism system of providing services or the processes of studying the production of innovative technologies in tourism sphere of Ukraine.

Мета. Розглянути проблематику життєдіяльності туристичного ринку в сучасних умовах коронавірусного періоду з акцентом на адаптацію механізму туристичного обслуговування, перебудову людської свідомості та на пошуки шляхів оптимізаційної реалізації нових підходів у практичній роботі туристичних агенцій і вищих навчальних закладів, які готують фахівців туристичної індустрії. Методика. Використані аналітичний, статистичний, порівняльно-географічний методи. Апробація. Основні концептуальні питання щодо проблематики існування туристичної сфери України в період коронавірусу, були озвучені на дистанційній Всеукраїнській науково-практичній конференції «Український туризм в умовах корона та пост коронавірусного періоду: антикризові сценарії, міжнародний досвід, кращі практики», яка була організована за сприянням кафедри географії України та кафедри країнознавства та туризму Київського національного університету імені Тараса Шевченка, до роботи якої були запрошені фахівці-практики туристичної галузі, представники держустанов, дотичних до туризму, викладачі вишів міста Києва та України. Наукова новизна. В рамках сучасної життєдіяльності людства, відкорегованого останнім спалахом пандемії всесвітнього масштабу COVID-19, виникла низка проблем економічного, політичного, соціального, господарського, освітнього та загального людського характеру, вирішення яких потребує суттєвого переосмислення існуючої ситуації у суспільстві та наданні пропозицій щодо нового формату подальшого життя людства та, зокрема, в Україні. Враховуючи особливості розвитку туризму в кожній окремо взятій країні, першочерговими плановими діями повинна стати розробка та впровадження «Дорожньої карти туристичного розвитку в Україні», в якій будуть прописані основні положення щодо практичної реалізації програми в період коронавірусу та етапу виходу з пост коронавірусного періоду. В статті аналізується міжнародний досвід реалізації таких програм, оцінюється фактичний матеріал, який стосується запровадження «Дорожньої карти» в умовах роботи українського туристичного ринку. Практична значимість. В статті піднімаються непрості питання, що стосуються реалій сучасного життя людей в рамках діяльності туристичної сфери України, з її проблемами, викликами та практичними рішеннями. Матеріали публікації можуть бути використані під час навчального процесу у вищих навчальних закладах, що здійснюють підготовку фахівців для української туристичної індустрії, практичній діяльності туристичних операторів і агенцій, в процесі роботи департаментів та фахових установ, які дотичні до туристичної системи надання послуг або до процесів вивчення питань впровадження інноваційних технологій у туристичну сферу України.
Сучасні реалії діяльності туристичного ринку України в коронавірусний період: виклики та практичні рішення
Keywords: короно вірус; виклики та реалії сучасного життя; пандемія; дорожня карта; туристичний ринок України; міжнародний досвід; перспективні рішення; корона вирус; вызовы и реалии современной жизни; пандемия; дорожная карта; туристический рынок Украины; международный опыт; перспективные решения; corona virus; challenges and realities of modern life; pandemic; roadmap; Ukrainian tourism market; international experience; promising solutions